Social Changes in the Post-Tsunami Banda Aceh City - Ismail Ismail; Salahuddin S; Amirulkamar Amirulkamar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Post-Tsunami Aceh has a significant impact on the people of Banda City, especially during and after rehabilitation and reconstruction has caused dependence and various kinds of social problems as a problem that arises so that social change occurs. The social change of the people of Banda Aceh City does not all lead to positive things, but also the changes refer to the negative direction. The social change in question is a change in the social value of the people of Banda Aceh due to assistance (cash for work) given to the community during the rehabilitation and reconstruction so that social changes occur. This study aims to examine and describe why social change occurred in the people of Banda Aceh after the tsunami using a qualitative approach. Data obtained through observation and interviews with various speakers. Determination of informants was done by purposive sampling with consideration of the informants were part of the community of Banda Aceh and people who survived the tsunami disaster. To analyze the research researchers used the theory of social change. The results showed that after the tsunami there had been a social change in the people of Banda Aceh City, there were positive changes, some were negative. Positive changes in the community feel that many help so that they can meet their needs in the short term, while the larger negative impacts, especially regarding social values such as the level of community participation in Banda Aceh in the construction of village development decrease, are evident from the fading of mutual cooperation inherent in community members and weak social responsibility resulting from dependence and individualistic attitudes